Standard generators of finite fields and their cyclic subgroups. (July 2023) - Lübeck, Frank
Abstract: We define standard constructions of finite fields, and standard generators of (multiplicative) cyclic subgroups in these fields. The motivation is to provide a substitute for Conway polynomials which can be used by various software packages and in collections of mathematical data which involve finite fields.